2013
DOI: 10.1001/jama.2013.281718
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Bypass Graft Surgery vs Percutaneous Interventions in Coronary Revascularization

Abstract: IMPORTANCE Ischemic heart disease is the leading cause of death globally. Coronary artery bypass graft (CABG) surgery and percutaneous coronary intervention (PCI) are the revascularization options for ischemic heart disease. However, the choice of the most appropriate revascularization modality is controversial in some patient subgroups. OBJECTIVE To summarize the current evidence comparing the effectiveness of CABG surgery and PCI in patients with unprotected left main disease (ULMD, in which there is >50% le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
146
0
10

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(159 citation statements)
references
References 46 publications
3
146
0
10
Order By: Relevance
“…Sixty-one (7.8%) patients had histories of preoperative CVD events. Among these patients, 46 experienced CAD, which were acute myocardial infarction (12), PCI (15), coronary artery bypass grafting (three), and angina pectoris (16). Sixteen experienced cerebrovascular disease, which were cerebral infarction (11) and cerebral hemorrhage (five).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty-one (7.8%) patients had histories of preoperative CVD events. Among these patients, 46 experienced CAD, which were acute myocardial infarction (12), PCI (15), coronary artery bypass grafting (three), and angina pectoris (16). Sixteen experienced cerebrovascular disease, which were cerebral infarction (11) and cerebral hemorrhage (five).…”
Section: Resultsmentioning
confidence: 99%
“…Coronary revascularization, either by percutaneous coronary intervention (PCI) or coronary artery bypass grafting, may be indicated in patients with flow-limiting coronary stenosis to reduce myocardial ischemia and related adverse clinical manifestations (10)(11)(12). In addition to acute coronary syndrome, revascularization for stable coronary artery disease (CAD) was performed at our institution according to the 2014 European Society of Cardiology and the European Association for Cardio-Thoracic Surgery guidelines on myocardial revascularization (13).…”
Section: Clinical Eventsmentioning
confidence: 99%
“…These mechanisms not only are implicated in the progression of clinically significant coronary artery disease but may also jeopardize long-term PCI results [29][30][31]. Accordingly, concerns have been raised regarding PCI in DM patients, especially in case of multivessel disease, which prompted extensive research exploring the potential superiority of surgical revascularization [32]. Although randomized controlled trials suggested a competitive efficacy of bypass surgery over PCI in diabetics with complex multivessel disease, it is routine practice worldwide to refer these patients to the catheterization laboratory in a significant proportion of cases [33].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal revascularization strategy for patients with multivessel coronary artery disease (CAD) remains still debated (1)(2)(3). The decision to recommend coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) should be driven by a comparison of the short-term and long-term effect on outcomes.…”
mentioning
confidence: 99%